2019
DOI: 10.1155/2019/4383269
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants in Cirrhotic Patients: Current Evidence and Clinical Observations

Abstract: The introduction of Direct Oral Anticoagulants (DOACs) to the pharmaceutical market provided patients and clinicians with novel convenient and safe options of anticoagulation. The use of this class of medications is currently limited to venous thromboembolic therapy and prophylaxis, in addition to stroke prophylaxis in patients with nonvalvular atrial fibrillation. Despite their altered hemostasis, patients with cirrhosis are thought to be in a procoagulant state and thus prone to thrombus formation. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 58 publications
(70 reference statements)
0
29
0
Order By: Relevance
“…These agents have been most extensively studied in patients with venous thromboembolism and nonvalvular atrial fibrillation . While using DOACs in cirrhosis, the dual concerns are of increased risk of adverse events because of alterations in the already compromised coagulation cascade in liver disease (true for any anticoagulant) and increased half‐life because of predominant hepatic metabolism . The hepatic metabolism of apixaban, rivaroxaban, edoxaban, and dabigatran is 75%, 65%, 50%, and 20%, respectively .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents have been most extensively studied in patients with venous thromboembolism and nonvalvular atrial fibrillation . While using DOACs in cirrhosis, the dual concerns are of increased risk of adverse events because of alterations in the already compromised coagulation cascade in liver disease (true for any anticoagulant) and increased half‐life because of predominant hepatic metabolism . The hepatic metabolism of apixaban, rivaroxaban, edoxaban, and dabigatran is 75%, 65%, 50%, and 20%, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 While using DOACs in cirrhosis, the dual concerns are of increased risk of adverse events because of alterations in the already compromised coagulation cascade in liver disease (true for any anticoagulant) and increased half-life because of predominant hepatic metabolism. 20 The hepatic metabolism of apixaban, rivaroxaban, edoxaban, and dabigatran is 75%, 65%, 50%, and 20%, respectively. 21 Long-term use of ximelagatran (first DOAC) had shown a significant risk of hepatotoxicity, leading to its withdrawal from the market.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world data on the use of DOACs in patients with CLD are continuously accumulating. Several new studies have been published since the release of the latest guidelines [67] and previous reviews on the use of DOACs in patients with cirrhosis [5,[74][75][76]. Original studies evaluating the use of DOACs vs traditional anticoagulants in patients with CLD are reported in Table 1 [77][78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: Evidence From Real-world Studiesmentioning
confidence: 99%
“…Upper endoscopy should be performed in all cirrhotic patients to screen for oesophageal varices in order to reduce the bleeding risk before starting any type of anticoagulant: treatment with either non-selective beta-blockers or endoscopic variceal ligation (EVL) is recommended based on varices size and risk of bleeding [76,99].…”
Section: A Practical Approach To the Prescription Of Doacsmentioning
confidence: 99%
“…42,62,69 The presence of severe thrombocytopenia (platelets < 50 Â 10 9 /L) has been suggested to be associated with a higher risk of bleeding in cirrhotic patients; however, the results are conflicting. 27,54,55,70 When DOACs are compared with traditional anticoagulants, although both treatments display similar safety profile in terms of total bleeding episodes, DOACs have less cerebral hemorrhage than traditional anticoagulants, 71,72 particularly VKAs. 73,74 However, another study found similar risks in major bleedings 64 and the need of further studies is evident.…”
Section: Anticoagulationmentioning
confidence: 99%